USE OF 3D RESOURCES IN TEACHING THE SCIENCE OF "INFROMATICS AND INFORMATION TECHNOLOGIES" - Quramboyev Islomjon Nuraddin ugli (Galaxy International Interdisciplinary Research Journal, 2024)
This article presents the content and forms of using 3D format resources in teaching "Informatics and Information Technologies" in secondary schools. The effectiveness of using the 3D format electronic manual created for teachers of computer science and information technology in general education schools is highlighted.